2005
DOI: 10.1063/1.1852708
|View full text |Cite
|
Sign up to set email alerts
|

Humidity effect on electrical performance of organic thin-film transistors

Abstract: Humidity dependence of electrical performance of p-channel organic thin-film transistors ͑OTFTs͒ with various semiconductor compounds has been investigated. All devices showed decreased current output and mobility as the relative humidity ͑RH͒ was increased. The moisture sensitivity of the OTFT saturation current depends on the device geometry ͑bottom or top contact device͒ and channel length. The OTFT configuration with a short channel length and bottom contact was most affected by humidity compared to the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
179
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(192 citation statements)
references
References 19 publications
8
179
0
3
Order By: Relevance
“…Sementara tegangan ambang bergeser ke arah positif, dari sekitar 1 V ke 2 V. Baik pada MOSFET pentacene bottomcontact maupun top-contact, pergeseran tegangan ambang ke arah positif mengindikasikan bahwa muatan yang bergerak (mobile charges) bisa diinduksikan pada lapisan semikonduktor oleh molekul uap air, sehingga tegangan gate positif yang besar dibutuhkan untuk mengompensasi muatan hole untuk mematikan MOSFET tersebut [12]. Semikonduktor organik seperti pentacene cenderung membentuk grain yang kecil pada elektrode sehingga ukuran grain dekat elektrode drain dan source menjadi kecil.…”
Section: Issn 2301 -4156unclassified
See 1 more Smart Citation
“…Sementara tegangan ambang bergeser ke arah positif, dari sekitar 1 V ke 2 V. Baik pada MOSFET pentacene bottomcontact maupun top-contact, pergeseran tegangan ambang ke arah positif mengindikasikan bahwa muatan yang bergerak (mobile charges) bisa diinduksikan pada lapisan semikonduktor oleh molekul uap air, sehingga tegangan gate positif yang besar dibutuhkan untuk mengompensasi muatan hole untuk mematikan MOSFET tersebut [12]. Semikonduktor organik seperti pentacene cenderung membentuk grain yang kecil pada elektrode sehingga ukuran grain dekat elektrode drain dan source menjadi kecil.…”
Section: Issn 2301 -4156unclassified
“…Gbr. 7 menunjukkan bahwa MOSFET pentacene bottom-contact lebih sensitif terhadap kelembaban dibandingkan dengan MOSFET pentacene top-contact, sehingga untuk masa depan, MOSFET pentacene bottom-contact bisa diaplikasikan sebagai sensor kelembaban karena sensitivitasnya yang baik dibandingkan MOSFET pentacene top-contact [12].…”
unclassified
“…the combination of these two effects leads to electrical parameters degradation [24] [25] such as mobility, threshold voltage and I on /I off ratio. It has been reported that, the diffusion of impurities such as polar water molecules into grain boundaries changes the intermolecular interactions in those regions, increasing energy barrier for charge carrier intergrain transport or ions associated with water screen the electric field at the channel and lower the concentration of gate-induced mobile carriers [26]. All of the mechanisms would lead to reduce the performances of Device 1.…”
Section: Electrical Characterization and Pentacene Morphologymentioning
confidence: 99%
“…Device-to-device current uniformity over a large area is still difficult to attain due to factors such as the randomness inherent in material crystallization [2], bias-and temperaturedependent mobility [3], contact effects [4,5] and moisture-or oxygen-related instability [6]. Of great consequence to applications are also the resolution and repeatability of patterning by large-area techniques.…”
Section: Introductionmentioning
confidence: 99%